OPTIMIZING CORN HARVEST WASTE AS A COMMUNITY ECONOMIC, IMPROVEMENT IN TAWANGREJO VILLAGE, GEMARANG, DISTRICT, MADIUN REGENCY - Soemarsono, Prinintha Nanda; Nabila, Lady Savita; Syafi'ah, Kamilatus; Pratama, Rehan Meihendra; Pramesti, Mutiara Putri; Kusuma, Juan; Prananda, Ariel Syalia; Cahyani, Larasati Puji; Hapsari, Aulia Arum; Maulana, Isya' Putra (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Corn is the second largest commodity in Tawangrejo Village, Gemarang District, Madiun Regency with a harvest reaching 3 tonnes in 2023. The large corn harvest is in line with the corn waste produced at the end of each harvest period. Until now, corn waste is still used as animal feed in small quantities and the rest is burned, resulting in air pollution around Tawangrejo Village. The work program of "KKN-BBK 2 Universitas Airlangga" aims to educate the public to optimize corn harvest waste while providing additional income from selling these handicraft products through digital marketing. The short-term result of this activity is that the people of Tawangrejo Village can make crafts from corn husk waste to become furniture decorations and brooches. Apart from that, the people of Tawangrejo Village are also able to create accounts on the marketplace and know marketing strategies that can be applied easily. The expected long-term result of this activity is that the income of the people of Tawangrejo Village can increase. For sustainability activities, training should be carried out regularly so that people can hone their creativity more deeply and become experts in making crafts. Apart from that, education regarding interesting marketing methods is also carried out regularly so that the public understands better and can be implemented in other products.